(untitled) (Archives of Mechanics - Test, 1996)
We derive some explicit formulae for heteroclinic pairs for scalar ordinary differential equations of the form u" + vλ(u)u’ - su(u - a)(u - 1)(1 + Ï•(u)) = 0, where λ is an arbitrary polynomial in Ï• and is properly chosen. The results are used in a simple model of plasma sustained by a laser beam.